Social cues & cyberbullying in facebook : the effects of flaming messages, friend count and anonymity on cyberbullying behaviors - Chan, Hui Ling (2014)
The current research seeks to investigate cyberbullying behaviors on Social Networking Sites (SNSs) by studying the effects of message, receiver and sender characteristics within one such popular platform, Facebook. Facebook, unlike older computer-mediated platforms, possesses distinct features and usage cultures, with one such example being the greater extent to which users disclose about their personal identity. The effect of such social cues and user behavioral patterns on Facebook towards cyberbullying behaviors is still not fully understood. In this study, we apply the communication model to understand how the frequency of cyberbullying activity, friend count and anonymity within Facebook can affect cyberbullying intentions and perception towards a potential cyberbully victim. A 2 x 2 x 2 factorial experimental design was created to examine the variables in this study. 200 undergraduates between 19 and 24 of age were recruited and randomly assigned to one of the eight experimental conditions. From the results, we found that anonymity and a greater frequency of cyberbullying activity increased the intention of users to want to cyberbully a victim. Also, a low-friend count and a greater frequency of cyberbullying activity can create a negative perception of the victim’s personality, which may lead to more online victimization. Implications of the results are discussed in the report.